Primary and secondary host selection by Ips typographus depends on Norway spruce crown characteristics and phenolic-based defenses - Korolyova, Nataliya; Buechling, Arne; Lieutier, François; Yart, Annie; Cudlín, Pavel; Turčáni, Marek; Jakuš, Rastislav (Plant science, 2022)
Climate change is expected to intensify bark beetle population outbreaks in forests globally, affecting biodiversity and trajectories of change. Aspects of individual tree resistance remain poorly quantified, particularly with regard to the role of phenolic compounds, hindering robust predictions of forest response to future conditions. In 2003, we conducted a mechanical wounding experiment in a Norway spruce forest that coincided with an outbreak of the bark beetle, Ips typographus. We collected phloem samples from 97 trees and monitored tree survival for 5 months. Using high-performance liquid chromatography, we quantified induced changes in the concentrations of phenolics. Classification and regression tools were used to evaluate relationships between phenolic production and bark beetle resistance, in the context of other survival factors. The proximity of beetle source populations was a principal determinant of survival. Proxy measures of tree vigor, such as crown defoliation, mediated tree resistance. Controlling for these factors, synthesis of catechin was found to exponentially increase tree survival probability. However, even resistant trees were susceptible in late season due to high insect population growth. Our results show that incorporating trait-mediated effects improves predictions of survival. Using an integrated analytical approach, we demonstrate that phenolics play a direct role in tree defense to herbivory.
Keywords: brouci; floém; Catechin; Resistance; Animals; Herbivory; Phenols; Phloem; Tree survival; Crown defoliation; smrk; zvířata; Primary attraction; Coleoptera; Bark beetle outbreak; Picea; fenoly; býložravci